Motivational interviewing in child welfare services: a systematic review - Hall, Martin T. (Child maltreatment, 2020)
Families in the child welfare (CW) system who cannot be engaged in services are at high risk of negative outcomes. As motivational interviewing (MI) has been shown to improve engagement in similar contexts. This study aimed to systematically review MI with CW families as well as MI training with CW workers and social work students training to become CW workers. The review used Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and searched multiple databases in June 2018. In September 2019, the initial search was repeated with additional searches to identify gray literature. Eight studies described the acquisition of MI among CW workers or student trainees, and 11 studies evaluated the impact of MI on families in CW. MI’s impact on some family outcomes, such as engagement in services, was mixed, though MI paired with other evidence-based treatments showed positive effects. With regard to training CW workers and students in MI, differences in training duration, intensity, and modality make conclusions difficult, though trainees generally described MI favorably and some studies showed training increased worker empathy and self-efficacy. Importantly, few published studies have evaluated whether MI-trained CW workers impact out-of-home-care placement, and no studies have evaluated their impact on maltreatment.